Role of Hippophae rhamnoides L. in the Management of Depression by Regulating Hyperhomocysteinemia: Role of Hippophae rhamnoides L. in the Management of Depression by Regulating Hyperhomocysteinemia - Dubey, G. P. (International Journal of Pharmaceutical & Biological Archive, 2019)
Depression is one of the major health burden in almost all the societies particularly in urban community. As per the World Health Organization, depression will be the second largest disease burden due to the urban way of lifestyle. The modern era is full of stress and strains the people are living in the most competitive society than the previous year. Although many antidepressant drugs have been develop to manage anxiety, stress and depression due to adverse side reaction, most of the drug could show satisfactory results. Considering the above fact, we have selected a drug Hippophae rhamnoides which contain many phyto molecules showing preventing role of anxiety and depression by regulating some of the biochemical parameters.